Implementation of Freedom To Learn in Higher Education: Perceptions of Students, Lecturers, and Administration Staff - Christine Dwi Karya Susilawati; Se Tin Se Tin; Bernard Rhenaldi Sutedja (Jurnal Akuntansi, 2023)
This study aims to explain the implementation of Free Learning - Independent Campus (MBKM) in a private university in West Java. Data was collected through a questionnaire via google link and analyzed descriptively. A total of 2,038 students, 257 lecturers and 190 administrative staff were sampled. Studies focus on knowledge, involvement, and impact of MBKM. The results of the study show, first, there are still many students, lecturers and education staff who know little and do not even know and understand the MBKM program; Second, information about MBKM is mainly obtained from internal universities; Third, the majority of lecturers contribute and play an active role in encouraging students to participate in MBKM activities; Fourth, the involvement of educational staff in the implementation of MBKM is still below 50% and they are already involved in administration, management, supervision and technical service functions; Fifth, MBKM provides additional competencies and skills, increases hard-skills and soft-skills, improves the learning process and lecturer capacity, fulfills graduate learning outcomes. This study provides a recommendation that there is a great need for sustainable socialization of the MBKM program with the aim of increasing understanding and eliminating misunderstandings about the MBKM program. Keywords: MBKM Implementation, Knowledge, Engagement, and Impact